Asuhan Penanggulangan Trismus Pasca Odontektomi pada Ny Fa dengan Terapi Panas - Siregar, Nelly Fitriani; Sodja Laela, Dewi; Fatikhah, Nurul; Nurnaningsih, Hera (Poltekkes Kemenkes Bandung, 2025)
Trismus is a complication that often occurs after odontectomy. Heat therapy is a common treatment to reduce inflammation and pain due to trismus. Dental and oral therapists have an important role in providing post-surgical care, including the application of heat therapy. This case report aims to describe the process of dental and oral health care for Mrs. AF with post-odontectomy trismus treated with heat therapy. This research is a case report with the concept of dental and oral health care which consists of the process of assessment, diagnosis, planning, implementation and evaluation for Mrs. FA clients. The patient showed a reduction in the incidence of trismus from 2.5 cm to 3.5 cm after being given heat therapy using a hot-pack and physiotherapy. Clients are given hot-packs and compressed for about 15 minutes 3 times a day for 1 week. Patients also report decreased pain and are able to perform oral care independently with proper technique. Heat therapy can be an effective option in reducing the symptoms of post-odontectomy trismus. Dental and oral health care that includes health education can improve the patient's quality of life.